From Social Bonds to Business Performance: Exploring the Dual Mediation of Online and Offline Social Capital in Digital Innovation Context - Yuliza; Ahmad Dafit; Nur, Sofyan Ashari (Universitas Tidar, 2025)
This study investigates the impact of digital innovation on the business performance of MSMEs through the mediating roles of online and offline social capital. Despite the rapid digital transformation among MSMEs in Central Java, technology adoption has not consistently translated into improved business outcomes, highlighting a gap between digital innovation and performance. Using a quantitative, cross-sectional survey approach, data were collected from 180 MSME respondents and analyzed with Structural Equation Modeling (SEM-AMOS). The results reveal that digital innovation significantly enhances both online and offline social capital, yet it does not directly influence business performance. Instead, online and offline social capital fully mediate the relationship between digital innovation and business performance. These findings suggest that digital innovation alone is insufficient to drive business success unless accompanied by strong relational networks, trust, and collaboration among MSME actors. The study underscores the importance of fostering community-based digital empowerment and hybrid (online–offline) connectivity strategies to strengthen MSME sustainability and competitiveness in the digital economy era.